Free Fibula Reconstruction of Distal Tibial Defects After Sarcoma Surgery. Issue 6 (June 2015) - Scaglioni, Mario Francesco Carlo; Arzi, Ravit Yanko; Gur, Eyal; Amotz, Oded Ben; Barnea, Yoav; Kollender, Yheuda; Meller, Isaak; Bickels, Jacob; Dadia, Shlomo; Zaretski, Arik
Abstract : Abstract: Distal tibial tumor ablation results in combined soft tissue and bone defect that involves the ankle joint. This area is unique and problematic because it combines low caliber limb size, relatively soft tissue deficiency, suboptimal bone and soft tissue healing ability, and the need to sustain increased mechanical loads. The management is difficult, controversial, and traditionally was treated by primary amputation. We present our experience with a limb sparing surgery using biological reconstruction. Between 2004 and 2007, 5 patients with malignant bone tumors of the distal tibia underwent tumor resection and reconstruction with free vascularized osteoseptocutaneous fibula flap. The average age was 33.2 years (range, 11–62 years). In all cases, a skin island was harvested and used for wound closure. Arthrodesis of the ankle joint was preformed in all patients. Double fixation system was used to provide stability and avoid flap rotation. All flaps survived. There were no major complications. One patient had partial loss of the skin paddle that was treated conservatively. Callous formation was documented after an average time of 4 months, partial weight bearing after an average time of 4 months, and full weight bearing after an average time of 11.5 months. All patients regained almost normal ambulation within a year.